ANALYSIS OF TRAILS AREA OF Tilapia (Oreochromis niloticus) ON GILL NET WITH DIFFERENT SHORTENINGS: - Hasrianti, Hasrianti (Jurnal Sains dan Teknologi Perikanan, 2021)
Knowledge of fish and fishing gear using fish behavior approaches is done to improve the effectiveness and efficiency of fishing. This study aims to determine the effect of shortening on the position of fish caught in gill nets. This research was carried out by using a flume tank with a size of 500 cm x 120 cm x 120 cm which was divided into 3 parts which were limited by waring insulation from polyethylene and nets made from PA monofilament material with treatment on shortening and hanging ratios namely using 40% and 60% shortening (hanging ratio 60% and 40%). Tilapia used in this experiment as many as 74 tails that have been measured are then placed in a maintenance tank. The experiment was carried out in 10 replications in each treatment (shortening and hanging ratio). The results showed that catching tilapia (Oreocromis niloticus) with 40% and 60% shortening with the same mesh size of 7.62 cm caught fish of different sizes. At 60% shortening fish tend to be caught gilled and have a larger size compared to fish caught on 40% shortening which ranges from 21 cm - 23.5 cm while on shortening 40% fish tend to be caught wedged and have sizes ranging from 19.10 cm - 21 cm. Percentage of bondage area to total length of tilapia on shortening was 40% greater, ranging from 4.10% - 7.14% compared to 60% shortening which ranged from 2.29% -3.48%.